Developing the Stuart Hall Library Zines Collection at Iniva. (27th March 2018) - Moran, Stephanie
Abstract : What is the importance of a zines collection to a contemporary visual arts library? What is their significance as research resources? This article explores the Stuart Hall Library zines collection, its history, management and use, and its role the context of the wider collection. It examines the collection's strengths and areas for development, including cataloguing and visibility. Key titles in the collection are described, and some of the themes and subjects covered. Local working practices and zine related activities are also discussed.